Traffic congestion and blood pressure elevation: A comparative cross‐sectional study in Lebanon. Issue 12 (10th October 2017) - Bou Samra, Patrick; El Tomb, Paul; Hosni, Mohammad; Kassem, Ahmad; Rizk, Robin; Shayya, Sami; Assaad, Sarah
Abstract : This comparative cross‐sectional study examines the association between traffic congestion and elevation of systolic and/or diastolic blood pressure levels among a convenience sample of 310 drivers. Data collection took place during a gas station pause at a fixed time of day. Higher average systolic (142 vs 123 mm Hg) and diastolic (87 vs 78 mm Hg) blood pressures were detected among drivers exposed to traffic congestion compared with those who were not exposed ( P <.001), while controlling for body mass index, age, sex, pack‐year smoking, driving hours per week, and occupational driving. Moreover, among persons exposed to traffic congestion, longer exposure time was associated with higher systolic and diastolic blood pressures. Further studies are needed to better understand the mechanisms of the significant association between elevated blood pressure and traffic congestion.